Incidence and predictors of difficult mask ventilation and intubation - Prerana N Shah; Vimal Sundaram (Wolters Kluwer Medknow Publications, 2012)
Background: This study is aimed to determine the incidence and predictors of difficult and impossible mask ventilation. Materials and Methods: Information like age, snoring history, obstructive sleep apnea, dental and mandibular abnormalities, macroglossia, grading like SLUX, Mallampatti, Cormack Lehanne, atlantooccipital extension, presence of beard or moustache, mouth opening were collected. During mask ventilation, the information related to the ventilation and intubation was collected. All variables found to be significant in univariate analysis were subjected to the multivariate logistic regression model to identify independent predictors of measured outcome. Results: Difficult mask ventilation (DMV) was observed in 30 male patients and 9 female patients. Of the 40 patients who had difficult intubation (DI), 7 patients had both DMV and intubation and 1 patient was of impossible mask ventilation/ intubation. Snoring was the lone significant risk factor for DMV. The risk factors identified for DI were snoring, retrognathia, micrognathia, macroglossia, short thick neck, Mallampatti grade [III/IV], abnormal SLUX grade, Cormack Lehanne grade [II,III/IV], abnormal atlantooccipital extension grading, flexion/extension deformity of neck, protuberant teeth, cervical spine abnormality, mouth opening < 3 cm, and BMI > 26 kg/m 2 . BMI > 26 kg/m 2 and atlantooccipital extension grade > 3 were independent risk factors for DI and the presence of two of the variables made the sensitivity and specificity of 43% and 99% respectively with a positive predictive value of 74%. Conclusions: The predictive score may lead to a better anticipation of difficult airway management, potentially deceasing the morbidity and mortality resulting from hypoxia or anoxia with failed ventilation.